Proceedings of the XI International Congress of Egyptologists, Florence, Italy 23-30 August 2015 - Guidotti, M. Cristina,; Rosati, Gloria, (Archaeopress Egyptology., 2017)
The eleventh International Congress of Egyptologists took place at the Florence Egyptian Museum (Museo Egizio Firenze), Italy in August 2015. The conference was organised by the International Association of Egyptologists (IAE), the Soprintendenza Archeologia della Toscana (Ministero dei Beni e delle Attivitá Culturali e del Turismo), CAMNES (Center for Ancient Mediterranean and Near Eastern Studies), the University of Florence (SAGAS department), and with the support of the Istituto Lorenzo de' Medici. This volume of the conference proceedings presents approximately 130 peer-reviewed papers alongside a selection of posters.